Adiponectin and leptin in overweight/obese and lean women with polycystic ovary syndrome. (April 2015) - Chen, Chin-I; Hsu, Ming-I; Lin, Shyh-Hsiang; Chang, Yuan-Chin I.; Hsu, Chun-Sen; Tzeng, Chii-Ruey
Abstract Aim: The objective of this study was to evaluate the adiponectin and leptin levels in overweight/obese and lean women with polycystic ovary syndrome (PCOS). Design: This was a retrospective study. Patients: Of the 422 studied patients, 224 women with PCOS and 198 women without PCOS were evaluated. Main outcome measure(s): Insulin resistance and the metabolic components were assessed. The adiponectin and leptin levels were also evaluated. Results: Adiponectin was negatively correlated with insulin resistance, body mass index (BMI), and total testosterone, triglyceride, and low-density lipoprotein (LDL) levels; conversely, leptin reversed the aforementioned reaction and was negatively correlated with adiponectin levels. The adiponectin to leptin ratios were significantly lower in PCOS women than in those without PCOS. Compared to women with non-PCOS, overweight/obese women with PCOS had lower serum adiponectin levels than women without PCOS, which was not the case for lean women. Conversely, lean women with PCOS had higher serum leptin levels than those without PCOS, which was not the case for overweight/obese women. Conclusions: Adipose tissue might play an important role in the metabolic complications in women with PCOS. To study the impact of obesity biomarkers in women with PCOS, overweight/obese and lean women should be considered separately.